GERAKAN SOSIAL POLITIK ISLAM DUNIA (Asas Perubahan Skenario Politik Negara) - Jhon Afrizal (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Emergence of Islamic political movements in the world today, has caused great concern for the West. Islam is considered a force that would threaten the hegemony of the West (USA and its allies) around the world. and there is no other way for them except to hinder and even destroy those movements.Revival of Islam to civilization at the present time, has begun in the Middle East countries. Turbulence and popular movements overthrow the dictator has been supported by the USA and its allies. The fall of the regime of Ben Ali in Tunisia, Hosni Mubarak in Egypt, Abdullah Saleh in Yemen and Muammar Gaddafi in Libya and now in the Syrian regime will fall forward thoghut Hafiz al-Assaad. And this shows (to the west) that Islam will appear as the holder of the reins of government in all countries bependuduk Islamic majority. One group or the most influential movement in the revival and political movements duniaIslam is the Muslim Brotherhood faction in Egypt and spread throughout most of the Islamic countries. Many factors led to the Islamic Reform Movement, among others: Effect of infidel countries, inequality ways of thinking among Islamic organizations, western lifestyle trend that began in the Islamic countries, the desire to gain power among certain segments of the name of Islam, Low levels of education, the economy is getting worse, and culture that deviates from the Qur'an and hadith, faith mistake, Shirk and bid'ah, To revive the Muslims from a very severe downturn, and other factors. in this case the West and its allies in various ways will do everything possible to prevent the Islamic reform movement in order to avoid in-many parts of the world, including by using reason in an effort to combat terrorism, but the real goal is to eradicate the Islamic teachings.